2013
DOI: 10.1007/s11916-013-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Sleep in Children

Abstract: Several scientific studies report a close relationship between sleep and headache: sleep changes may reflect the onset and increase of both duration and frequency of headache attacks. Variations in sleep architecture, together with a poor sleep hygiene in children, may indeed be responsible for the onset of headache and its development into a chronic disease. For a correct clinical management of children with headache, it is therefore fundamental to investigate their sleep habits, architecture and potential di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…There is also thought to be an association with sleep disorders in earlier childhood and later presentation of migraines or headaches. 27 Although most studies have not focused on a specific AYA population, those that have also demonstrated an interaction or association between headaches and sleep. [28][29][30] The relationship between sleep and pain for young people with juvenile idiopathic arthritis and other rheumatological conditions has more recently been explored.…”
Section: Sleep and Painmentioning
confidence: 99%
“…There is also thought to be an association with sleep disorders in earlier childhood and later presentation of migraines or headaches. 27 Although most studies have not focused on a specific AYA population, those that have also demonstrated an interaction or association between headaches and sleep. [28][29][30] The relationship between sleep and pain for young people with juvenile idiopathic arthritis and other rheumatological conditions has more recently been explored.…”
Section: Sleep and Painmentioning
confidence: 99%
“…It is known as sleep deprivation, or, on the contrary, a prolonged sleep, can favor the onset of headache, in particular migraine attack [41]. On the other hand, in many cases, and especially in children, sleep, spontaneous or induced by hypnotics, constitutes the decisive factor for resolution of a migraine attack [42].…”
Section: Headache and Psychiatric Disorders: Anxiety And Depressionmentioning
confidence: 99%
“…In a parallel way, Dyb et al [24] revealed higher incidence of comorbid mood and anxiety disorders (major depressive disorder, panic disorder, generalized anxiety disorder, and specific phobias) in children with migraine. At the same time, Bellini et al [7] as well as Arruda and Bigal [25] declared significantly higher association of behavioral and internalization symptoms among children and adolescents with migraine especially in those with high headache frequencies.…”
Section: Discussionmentioning
confidence: 88%
“…There is a bidirectional relationship between childhood migraine and sleep disturbances possibly due to sharing the same neuropeptides abnormalities including serotonin, dopamine, and/or melatonin [6]. Migraine sufferers often have trouble falling asleep, insufficient sleep, bedwetting, somnophobia, parasomnias, and excessive daytime sleepiness (EDS) which negatively influence the child's health and intellectual performance [7,8].…”
Section: Introductionmentioning
confidence: 99%